2021
DOI: 10.3389/fphys.2021.720898
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic Surgery in Cirrhosis Significantly Increases Portal Pressure in Preclinical Animal Models

Abstract: Background: Liver cirrhosis is a relevant comorbidity with increasing prevalence. Postoperative decompensation and development of complications in patients with cirrhosis remains a frequent clinical problem. Surgery has been discussed as a precipitating event for decompensation and complications of cirrhosis, but the underlying pathomechanisms are still obscure. The aim of this study was to analyze the role of abdominal extrahepatic surgery in cirrhosis on portal pressure and fibrosis in a preclinical model.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Recently, in animal models of cirrhosis, portal pressure was significantly elevated after extrahepatic injury and associated with clinical signs of decompensation. [40] Moreover, recent studies confirm significant reduction of postprocedural ACLF episodes and short-term mortality in patients with preoperative TIPS and patients with optimized TIPS stent diameter. [41,42] Organ/space SSIs affect deeper lying compartments, which might require antibiotic therapy with high tissue penetration.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, in animal models of cirrhosis, portal pressure was significantly elevated after extrahepatic injury and associated with clinical signs of decompensation. [40] Moreover, recent studies confirm significant reduction of postprocedural ACLF episodes and short-term mortality in patients with preoperative TIPS and patients with optimized TIPS stent diameter. [41,42] Organ/space SSIs affect deeper lying compartments, which might require antibiotic therapy with high tissue penetration.…”
Section: Discussionmentioning
confidence: 90%
“…Clinically significant portal hypertension might be a main driver promoting postsurgical ACLF. Recently, in animal models of cirrhosis, portal pressure was significantly elevated after extrahepatic injury and associated with clinical signs of decompensation 40 . Moreover, recent studies confirm significant reduction of postprocedural ACLF episodes and short-term mortality in patients with preoperative TIPS and patients with optimized TIPS stent diameter 41,42 …”
Section: Discussionmentioning
confidence: 95%
“…In ACLD patients, we can find changes in hepatic flow with the creation of arterio-venous fistulas, reduction in hepatocyte function with a decrease in proteins synthesis, and destruction of the bile canaliculi with a decrease in the ability to excrete metabolites through the bile [ 69 ]. Moreover, animal models demonstrated that extrahepatic surgery can increase portal pressure [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 Nevertheless, preceding findings highlighted the success of sham operation and/or common bile ligation combined with LPS or CCl 4 inhalation in establishing ACLF. [67][68][69] Recently, Karus et al 70 highlighted the combination of bile duct ligation, ethanol binge drinking, repetitive LPS injections, transnasal stool inoculation and cecal ligation and puncture, a complicated approach to generate a new rat model of cholestatic liver cirrhosis-developing ACLF. The differences in final outcomes might impede the selection and rational application of these models to investigate ACLF pathophysiology.…”
Section: Surrogate Animal Modelsmentioning
confidence: 99%